Transgenderism A Queer Theoretical Study In Okky Madasari's Bound Novel 2014 - Khotimah, Fadhillah Khusnul; , Dr. Phil. Dewi Candraningrum, M. Ed; , Titis Setyabudi, S.S., M. Hum (2016)
This research intends to describe how the process of being a transgender, obstacles encountered, and what kind of transgenderism is reflected in Okky Madasari's Bound. This research is a descriptive qualitative research which is done under the framework of Queer Theory. This research takes Okky Madasari's Bound as source of data. Some forms of its word, sentence, and dialogues are taken as primary data. This research shows that Sasana as a transgender experiences particular types of process of being transgender including the process of observing the opposite gender behavior, substituting, declaring new identity, finding the support, re-adapting behavior, declaring new identity to family, making decision, facing the obstacle to get the freedom. He has to face many significant obstacles such as: body trap, social stigmas, violence, powerlessness and poverty, depression, and family rejection. The kind of transgenderism is reflected in Bound novel is cross- dresser especially a drag queen.